Tenofovir to Prevent Hepatitis B Transmission in Mothers With High Viral Load. Issue 10 (October 2016) - Pan, Calvin Q.; Duan, Zhongping; Dai, Erhei; Zhang, Shuqin; Han, Guorong; Wang, Yuming; Zhang, Huaihong; Zou, Huaibin; Zhu, Baoshen; Zhao, Wenjing; Jiang, Hongxiu
Abstract : (Abstracted from N Engl J Med 2016;374:2324–2334) Hepatitis B virus (HBV), a leading cause of cirrhosis and liver cancer, is a serious health threat, and prevention of HBV transmission is an important part of the strategy to alleviate infection and its outcomes. Hepatitis B virus can be vertically transmitted from mothers to fetuses during childbirth, and infants who are untreated can consequently develop chronic infection.